2003
DOI: 10.1074/jbc.m300745200
|View full text |Cite
|
Sign up to set email alerts
|

The Calpain Domain of the Maize DEK1 Protein Contains the Conserved Catalytic Triad and Functions as a Cysteine Proteinase

Abstract: Development of the aleurone layer of maize grains requires the activity of the Defective kernel 1 (Dek1) gene, encoding a predicted 240-kDa membrane-anchored protein with a C terminus similar to animal calpain domain II&III. Three-dimensional modeling shows that DEK1 domain II contains a conserved calpain catalytic triad and that domain II&III has a predicted structure similar to m-calpain. Recombinant DEK1 domain II&III exhibits activity in the caseinolytic assay in the absence of calcium, although the activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 48 publications
2
71
1
Order By: Relevance
“…This hypothesis was based on the highly conserved active site of DEK1 compared with typical animal calpains as well as on the fact that DEK1-CALP displays calpain Cys proteinase activity in vitro (Wang et al, 2003). Here, we have shown that maize DEK1-CALP failed to complement the loss-of-aleurone cell phenotype in homozygous maize dek1 mutant endosperm under the control of the 27-kD g-Zein promoter.…”
Section: Dek1-calp Fails To Fully Complement the Dek1 Mutant Phenotypementioning
confidence: 81%
See 1 more Smart Citation
“…This hypothesis was based on the highly conserved active site of DEK1 compared with typical animal calpains as well as on the fact that DEK1-CALP displays calpain Cys proteinase activity in vitro (Wang et al, 2003). Here, we have shown that maize DEK1-CALP failed to complement the loss-of-aleurone cell phenotype in homozygous maize dek1 mutant endosperm under the control of the 27-kD g-Zein promoter.…”
Section: Dek1-calp Fails To Fully Complement the Dek1 Mutant Phenotypementioning
confidence: 81%
“…Although the three-dimensional structure of DEK1 is unknown, it has been speculated that the predicted extracellular portion of the molecule interacts with external ligands or membrane proteins representing positional information. Furthermore, we have proposed that external signals perceived by DEK1-MEM are transmitted via the calpain-like Cys protease (DEK1-CALP) predicted to be in the cytosol ( Figure 1A) (Wang et al, 2003). Third, DEK1 is ubiquitously expressed in the endosperm, fulfilling an important requirement for a protein involved in sensing and/or transmitting cell surface positional information (Lid et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, partial inhibition of the proteolysis by EGTA is indicative of a calcium-stimulated cysteine protease activity such as the maize DEK1, which belongs to the calpain family (27). DEK1 is a membrane-bound protein that contains a calpain catalytic triad, and it displays high structure homology in domains II and III to the animal small opticlobes (SOL), and SOHL (small homolog from human) calpains (28). In contrast to the animal calpains, DEK1 exhibits strong proteolytic activity in the absence of calcium that increases further in the presence of Ca 2ϩ , similar to what we observed in this study (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Homozygous cr4 endosperms lack patches of aleurone cells, and leaves of homozygous mutant plants are crinkly. Dek1 encodes a protein with 21 predicted transmembrane segments and a calpain-like protease in the C terminus (Lid et al, 2002;Wang et al, 2003). Homozygous dek1 endosperms almost entirely lack aleurone cells, and embryos are arrested at the globular stage of development (Lid et al, 2002).…”
mentioning
confidence: 99%